High-Resolution Imaging of Resolved Central Serous Chorioretinopathy Using Adaptive Optics Scanning Laser Ophthalmoscopy - Ooto, Sotaro; Hangai, Masanori; Sakamoto, Atsushi; Tsujikawa, Akitaka; Yamashiro, Kenji; Ojima, Yumiko; Yamada, Yoshihiko; Mukai, Hideo; Oshima, Susumu; Inoue, Takashi; Yoshimura, Nagahisa (Ophthalmology (Rochester, Minn.), 2010)
To compare pathologic changes in photoreceptors in eyes with resolved central serous chorioretinopathy (CSC) seen on high-resolution images obtained by adaptive optics scanning laser ophthalmoscopy (AO SLO) with visual acuity (VA) and findings on spectral-domain optical coherence tomography (SD OCT). Observational case series. Forty-five eyes of 38 patients with resolved CSC and 20 normal eyes of 20 volunteer subjects. All patients underwent a full ophthalmologic examination, SD OCT, and imaging with an original prototype AO SLO system fabricated using liquid crystal-on-silicon technology. Cone mosaic patterns and cone density on AO SLO images and VA in eyes with CSC. In normal eyes, AO SLO images showed a regular photoreceptor mosaic pattern and average cone densities 0.2, 0.5, and 1.0 mm from the central fovea of 67 900, 33 320, and 14 450 cones/mm 2. In eyes with CSC, cone densities were significantly lower at each distance from the central fovea ( P = 0.009 at 0.2 mm, P = 0.007 at 0.5 mm, and P = 0.004 at 1.0 mm), and 2 distinct cone mosaic patterns were seen. Group 1 CSC eyes had regular cone mosaic patterns with small dark regions. Group 2 CSC eyes had irregular mosaic patterns with large dark regions. Compared with group 1, group 2 had significantly lower average cone density and worse average logarithm of the minimum angle of resolution (logMAR) VA ( P<0.001). Mean cone density in eyes with disruptions in the photoreceptor inner and outer segment (IS/OS) junction or in the intermediate line on SD OCT images was significantly lower than that in eyes with an intact IS/OS junction or intermediate line ( P<0.001 for both). Cone density 0.2 mm from the central fovea correlated with logMAR VA and mean foveal thickness (1-mm diameter area) measured on SD OCT images ( P<0.001 for both). Adaptive optics SLO images showed abnormal cone mosaic patterns and reduced cone densities in eyes with resolved CSC, and these abnormalities were associated with VA loss, suggesting that AO SLO is a useful means to detect and measure cone abnormalities associated with VA loss in these eyes. Proprietary or commercial disclosure may be found after the references.